Identification of candidate microRNA biomarkers of mouse cholangiocyte injury by global miRNAome analysis - Lawrence Howell; Joseph P. Brown; Shiva Seyed Forootan; Ben Francis; Carolyn Jones; Lucia Livoti; Lorenzo Ressel; Emanuele Ricci; Martin Bushell; Chris Goldring (Toxicology and Applied Pharmacology, 2026)

An eight-founder wheat MAGIC population allows fine-mapping of flowering time loci and provides novel insights into the genetic control of flowering time - Laure Fourquet; Tobias Barber; Camila Campos-Mantello; Phil Howell; Beata Orman-Ligeza; Lawrence Percival-Alwyn; Gemma A. Rose; Hester Sheehan; Tally I. C. Wright; Friedrich Longin; Tobias Würschum; Dario Novoselovic; et al. (Theoretical and Applied Genetics, 2024)
Flowering time synchronizes reproductive development with favorable environmental conditions to optimize yield. Improved understanding of the genetic control of flowering will help optimize varietal adaptation to future agricultural systems under climate change. Here, we investigate the genetic basis of flowering time in winter wheat ( Triticum aestivum L.) using an eight-founder multi-parent advanced generation intercross (MAGIC) population. Flowering time data was collected from field trials across six growing seasons in the United Kingdom, followed by genetic analysis using a combination of linear modelling, simple interval mapping and composite interval mapping, using either single markers or founder haplotype probabilities. We detected 57 quantitative trait loci (QTL) across three growth stages linked to flowering time, of which 17 QTL were identified only when the major photoperiod response locus Ppd-D1 was included as a covariate. Of the 57 loci, ten were identified using all genetic mapping approaches and classified as ‘major’ QTL, including homoeologous loci on chromosomes 1B and 1D, and 4A and 4B. Additional Earliness per se flowering time QTL were identified, along with growth stage- and year-specific effects. Furthermore, six of the main-effect QTL were found to interact epistatically with Ppd-D1 . Finally, we exploited residual heterozygosity in the MAGIC recombinant inbred lines to Mendelize the Earliness per se QTL QFt.niab-5A.03 , which was confirmed to modulate flowering time by at least four days. This work provides detailed understanding of the genetic control of phenological variation within varieties relevant to the north-western European wheat genepool, aiding informed manipulation of flowering time in wheat breeding.

Systems analysis of miRNA biomarkers to inform drug safety - Amy L. Schofield; Joseph P. Brown; Jack Brown; Ania Wilczynska; Catherine Bell; Warren E. Glaab; Matthias Hackl; Lawrence Howell; Stephen Lee; James W. Dear; Mika Remes; Paul Reeves; et al. (Archives of Toxicology, 2021)
microRNAs (miRNAs or miRs) are short non-coding RNA molecules which have been shown to be dysregulated and released into the extracellular milieu as a result of many drug and non-drug-induced pathologies in different organ systems. Consequently, circulating miRs have been proposed as useful biomarkers of many disease states, including drug-induced tissue injury. miRs have shown potential to support or even replace the existing traditional biomarkers of drug-induced toxicity in terms of sensitivity and specificity, and there is some evidence for their improved diagnostic and prognostic value. However, several pre-analytical and analytical challenges, mainly associated with assay standardization, require solutions before circulating miRs can be successfully translated into the clinic. This review will consider the value and potential for the use of circulating miRs in drug-safety assessment and describe a systems approach to the analysis of the miRNAome in the discovery setting, as well as highlighting standardization issues that at this stage prevent their clinical use as biomarkers. Highlighting these challenges will hopefully drive future research into finding appropriate solutions, and eventually circulating miRs may be translated to the clinic where their undoubted biomarker potential can be used to benefit patients in rapid, easy to use, point-of-care test systems.

Proteomic profiling of murine biliary-derived hepatic organoids and their capacity for drug disposition, bioactivation and detoxification - Lawrence Howell; Rosalind E. Jenkins; Stephen Lynch; Carrie Duckworth; B. Kevin Park; Christopher Goldring (Archives of Toxicology, 2021)
Hepatic organoids are a recent innovation in in vitro modeling. Initial studies suggest that organoids better recapitulate the liver phenotype in vitro compared to pre-existing proliferative cell models. However, their potential for drug metabolism and detoxification remains poorly characterized, and their global proteome has yet to be compared to their tissue of origin. This analysis is urgently needed to determine what gain-of-function this new model may represent for modeling the physiological and toxicological response of the liver to xenobiotics. Global proteomic profiling of undifferentiated and differentiated hepatic murine organoids and donor-matched livers was, therefore, performed to assess both their similarity to liver tissue, and the expression of drug-metabolizing enzymes and transporters. This analysis quantified 4405 proteins across all sample types. Data are available via ProteomeXchange (PXD017986). Differentiation of organoids significantly increased the expression of multiple cytochrome P450, phase II enzymes, liver biomarkers and hepatic transporters. While the final phenotype of differentiated organoids is distinct from liver tissue, the organoids contain multiple drug metabolizing and transporter proteins necessary for liver function and drug metabolism, such as cytochrome P450 3A, glutathione- S -transferase alpha and multidrug resistance protein 1A. Indeed, the differentiated organoids were shown to exhibit increased sensitivity to midazolam (10–1000 µM) and irinotecan (1–100 µM), when compared to the undifferentiated organoids. The predicted reduced activity of HNF4A and a resulting dysregulation of RNA polymerase II may explain the partial differentiation of the organoids. Although further experimentation, optimization and characterization is needed relative to pre-existing models to fully contextualize their use as an in vitro model of drug-induced liver injury, hepatic organoids represent an attractive novel model of the response of the liver to xenobiotics. The current study also highlights the utility of global proteomic analyses for rapid and accurate evaluation of organoid-based test systems.